ANALISIS PEMBUATAN BRIKET BIOARANG LIMBAH TEMPURUNG KENARI (CANARIUM INDICUM) DENGAN BAHAN PEREKAT TEPUNG TAPIOKA - Fiyoliyandi Djangu; Dedie Tooy; Handry Rawung (Universitas Sam Ratulangi, 2018)
Abstract Walnut are native to Indonesia, which grows in many parts of the east, such as North Sulawesi and Maluku. Walnut shell is one of the Agricultural solid waste that has not been used optimally. Walnut shells have a physical structure that is hard enough to allow it to be used as charcoal, the use of walnut shells is still very lacking, so it takes the process of processing walnut shells into a more useful product. The purpose of this study is to make walnut shell briquettes and analyse content, ash content, briquette fuel that meet the Indonesian National Standard (SNI). The research was carried out for six months in two places, namely the Engineering Laboratory of the Faculty of Agriculture, Sam Ratulangi University Manado and the Laboratory of the Industry and Trade Standardization Research Institute.this study uses a descriptive method with different amounts of flour treatment (50 grams, 100 grams, 150 grams) and aims to observe the effect of adhesive material (tapioca flour) on the results of research, walnut shell briquettes have met the Indonesian National Standard (SNI). Keywords : walnut shell, tapioca adhesive, bioarang briquette